Validity and Reliability Assessment of Attitude Scales for Hepatitis B Vaccination Among Parents in Ho Chi Minh City, Vietnam - Huynh G; Pham DUB; Nguyen TV; Bui VQ; Nguyen TNH; Nguyen DD; Pham LA (Dove Medical Press, 2020)
Giao Huynh,1 Duong Uyen Binh Pham,2 Truong Vien Nguyen,1 Vinh Quang Bui,3 Thi Ngoc Han Nguyen,4 Dang Dung Nguyen,1 Le An Pham5 1Faculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 2Quality Assurance of Education, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 3Department of Pediatrics, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 4Infection Control Department, University Medical Center Ho Chi Minh City, Ho Chi Minh City, Vietnam; 5Center for Training in Family Medicine, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, VietnamCorrespondence: Giao Huynh; Duong Uyen Binh PhamUniversity of Medicine and Pharmacy at Ho Chi Minh City, 217 Hong Bang Street, District 5, Ho Chi Minh City, VietnamTel +84908608338; +84902660916Email hgiaoytcc@ump.edu.vn, p.d.uyenbinh@gmail.comBackground: Attitudes and beliefs could be associated with the low number of vaccinations in low- to middle-income countries such as Vietnam. This study aims to describe ways to develop and assess the attitudes towards Hepatitis B vaccination.Methods: A mixed-method study was carried out between April 2015 and July 2017. Qualitative data were gathered via semi-structured interviews and focus group discussions. The data were then analyzed thematically into four domains of the Health Belief Model (HBM) in order to design the structured questionnaire. The quantitative strand was followed by the evaluation of the reliability and the construct validity, for which data were obtained after interviewing 768 parents whose children aged from 12 to 24 months, who were receiving the vaccines as part of the Expanded Programme on Immunization (EPI) schedules at the Commune Health Centers.Results: The findings showed the content validity index value of 13 items ranged from 0.86 to 1.00. The factor analyses showed that 11 items remained in the final questionnaire after deleting 2 problematic items due to no relation to the total scales and revealed four factors (perceived susceptibility, perceived severity, perceived benefits, perceived barriers) that jointly accounted for 62.1% of the observed variances. All four factors have good internal consistency with a total Cronbach’s alpha of 0.735. A confirmatory factor analysis demonstrated the proposed factor model which fits well in four domains of HBM.Conclusion: Attitude scales for Hepatitis B vaccination based on HBM have been developed. This has confirmed to be a valid and reliable instrument that might be useful in assessing parents’ attitudes regarding Hepatitis B vaccination and may be used to promote interventions within the increasing vaccination coverage for Vietnamese children.Keywords: Hepatitis B, vaccination, children, reliability, Health Belief Model